Strength Analysis of the Floating Pier Structure with Passenger Ship 116 GT (Case Study: Sanur Harbor, Bali Province) - Buana, Eliezer Bertram Free; Sholihin, Sholihin; Sambodho, Kriyo (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2024)
The pier is one of the primary means of sea transportation that continues to be developed to support equity activities and advance the community's economy. Bali is one of the main tourist destinations in Indonesia. The construction of the Sanur Floating Pier will create good connectivity between regions in Bali, which can become an additional tourist destination so that tourists can vacation longer in Bali. The purpose of this study was to determine the strength of the floating jetty structure through an analysis of the loading received by the structure and the resistance of the piles so that they can carry out designs related to the installation of strong and safe floating dock piles. In the analysis process, the author uses the help of Plaxis V.8.6 software to model the soil and AutoCAD 2018 as a support system in making the floating dock pile installation layout. The analysis results show that the floating dock can accept the forces acting on the structure. The UE RPD 250 fender and the T-Head MT 20 type bollard are the right choices. The pile has a lateral force value (H) of 1907 kg with a deflection of 0.19 mm. The greater the number of piles installed on the floating pier, the stronger the structure is evidenced by the smaller pile settlement due to soil changes.